2014
DOI: 10.1080/09291016.2014.985002
|View full text |Cite
|
Sign up to set email alerts
|

Shift work tolerance and the importance of sleep quality: a study of police officers

Abstract: The aim of this study was to examine how subjective shift work tolerance was related to general health variables, with the expectation of inter-individual differences in the nature of this relation. A total of 740 employees of the Dutch Police force completed a questionnaire, covering seven health-related domains: sleep quality, sleep duration, need for recovery, fatigue, physical health, mental health, and worklife balance. Based on subjective reports of shift work tolerance, participants were classified as i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…An appropriate work-life balance and limited work-life conflict—largely nonexistent in the LHTD profession—is vital to improving the health and quality of life of all working populations. The effects of inadequate sleep, occupational stress and work-life conflicts applies to numerous other diverse occupations, including the healthcare industry, police officers, information technology, to name a few, particularly with new and emerging technologies that allow workers to work remotely and at all hours of the day or what is now referred to as ‘boundaryless’ work [31,41,121,122,123]. As described in the current study, the occupational milieu experienced by members of the long-haul trucking profession serves as a critical direct influence on the health and wellbeing of a vastly important population to the U.S. economy.…”
Section: Discussionmentioning
confidence: 99%
“…An appropriate work-life balance and limited work-life conflict—largely nonexistent in the LHTD profession—is vital to improving the health and quality of life of all working populations. The effects of inadequate sleep, occupational stress and work-life conflicts applies to numerous other diverse occupations, including the healthcare industry, police officers, information technology, to name a few, particularly with new and emerging technologies that allow workers to work remotely and at all hours of the day or what is now referred to as ‘boundaryless’ work [31,41,121,122,123]. As described in the current study, the occupational milieu experienced by members of the long-haul trucking profession serves as a critical direct influence on the health and wellbeing of a vastly important population to the U.S. economy.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the study from Radun et al 47 ) , identified fatigue to be a common concern for police officers, especially as a consequence of night work and the resulting motor-vehicle accident risk47 ) . These concerns were further built upon by another cross-sectional study which identified individual shift work tolerance as being an important factor influencing fatigue development48 ) ; when comparing Dutch police officers based on a subjective self-perception as intolerant, medium-tolerance and tolerance to shift work, the primarily related variables included sleep quality, need for recovery and fatigue48 ) . Another study involving Korean police officers also sought to investigate the variables impacting police officer health by studying job and psychosocial stress, as well as fatigue49 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Most people spend one-third of their lives sleeping [ 1 ]. Furthermore, sleep is essential to maintain good health as it helps revitalize and re-energize the body [ 2 , 3 , 4 ]. In addition, sleep is associated with weight management and longevity [ 5 , 6 , 7 ], and sleep quality is associated with self-report health, mood regulation, as well as feelings of anger, confusion, anxiety, and depression [ 8 , 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%